Study of the Bose-Einstein correlations of same-sign pions in proton-lead collisions - Aaij, Roel; Abdelmotteleb, A. S. W.; Abellan Beteta, C.; Abudinén, F.; Ackernley, T.; Adeva, B.; Adinolfi, M.; Adlarson, P.; Afsharnia, H.; Agapopoulou, C.; Aidala, C. A.; Ajaltouni, Z.; et al. (Journal of high energy physics, 2023)
Correlations of same-sign charged pions are analysed using proton-lead collision data collected by the LHCb experiment at a nucleon-nucleon centre-of-mass energy of 5.02 TeV, corresponding to an integrated luminosity of 1.06 nb−1. Bose-Einstein correlations are observed in the form of an enhancement of pair production for same-sign charged pions with a small four-momentum difference. The dependence of the correlation radius and the intercept parameter on the reconstructed charged-particle multiplicity is investigated. The measured correlation radii scale linearly with the cube root of the reconstructed charged-particle multiplicity, being compatible with predictions of hydrodynamic models on the collision system evolution.